2010
DOI: 10.4314/ajbr.v10i2.50617
|View full text |Cite
|
Sign up to set email alerts
|

The effect of chronic cement dust exposure on lung function of cement factory workers in sokoto, nigeria

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 4 publications
4
24
1
Order By: Relevance
“…21 The findings on pulmonary function parameters (the VC (vital capacity), FVC, FEV 1 , FEV 1 /VC ratio and PEFR values) in the study carried out by Yang 22 and his colleagues are consistent with the findings in this study. The findings by Al -Neaimi 16 and others, 6,17 were also similar to the findings in this study. These studies on cement dust exposure have demonstrated the observation of lower pulmonary function indices and impaired lung function.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…21 The findings on pulmonary function parameters (the VC (vital capacity), FVC, FEV 1 , FEV 1 /VC ratio and PEFR values) in the study carried out by Yang 22 and his colleagues are consistent with the findings in this study. The findings by Al -Neaimi 16 and others, 6,17 were also similar to the findings in this study. These studies on cement dust exposure have demonstrated the observation of lower pulmonary function indices and impaired lung function.…”
Section: Discussionsupporting
confidence: 82%
“…12 A study carried out on the workers of this cement factory in Kalambaina found that cement dust was deleterious to health of the workers. 6,7 The study found the vital capacity and forced expiratory volume for one second percent [FEV 1 %] were found to be significantly lower in the cement factory workers than in the control subjects. The haemoglobin concentration and packed cell volume were significantly lower than those of the control group while the white cell count and platelets were significantly higher in the cement factory workers than in the control group.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several cross sectional studies have found high prevalence of chronic respiratory symptoms (7,38,41,(49)(50)(51)(52)(53)(54) and reduction of lung function (7,41,53,(55)(56)(57).…”
Section: Chronic Respiratory Health Effectsmentioning
confidence: 99%